Distribution characteristics of integrons and correlation analysis of antibiotic resistance in urine isolated Enterobacter cloacae - Qiu, Xuedan; Zhang, Hui; Jiang, Min; Wu, Qiaoping (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aims to understand the distribution of integrons among Enterobacter cloacae isolated from clinical urine specimens in our hospital, as well as the molecular characteristics of the variable region resistance gene cassette of integron-positive strains and its relationship with drug resistance.MethodsWe collected a total of 80 strains of Enterobacter cloacae isolated from urine specimens of hospitalized patients in our hospital between August 2019 and July 2023, and conducted drug sensitivity testing on them. Polymerase Chain Reaction (PCR) technology was employed to screen these strains for Class 1, 2, and 3 integrons. Following this, the promoter and variable regions of integron-positive strains were amplified and sequenced. Additionally, Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR) was utilized for homology analysis of integron-positive strains.ResultsAmong the 80 clinical strains, Class 1 integrons were detected in 31 (38.8%) strains, and the following resistance gene cassettes were identified: aadA2, aadA1, aadB, aac(6’), and catB8. Three types of variable region promoters were observed: PcS (4 strains), PcW (7 strains), and PcH1 (17 strains), with consistently inactive downstream P2 promoters. Additionally, Class 2 integrons were detected in 5 (6.3%) strains, carrying the variable region resistance gene cassette dfrA1-sat2-aadA1. The promoters for Class 2 integrons were uniformly of the Pc2D-Pc2A-Pc2B-Pc2C type. No Class 3 integrons were detected. The strains containing integrons showed significantly higher resistance rates to ciprofloxacin, compound sulfamethoxazole, levofloxacin, gentamicin, amikacin, and tobramycin compared to those without integrons (P<0.05). 35 strains of Enterobacter cloacae carrying integrons are primarily classified into three genotypes: A, B, and C. These genotypes are mainly distributed in the urology department and Intensive Care Unit (ICU). The distribution of variable region gene boxes and promoter types is relatively concentrated in the same genotype.ConclusionOur study confirmed that Enterobacter cloacae isolated from urine samples predominantly carries Class 1 integrons with an extended array of antibiotic-resistant genes. For future research, it is recommended to explore additional resistance mechanisms and evaluate the effectiveness of new therapeutic strategies. Clinicians should be vigilant about the possibility of clonal dissemination and implement enhanced infection control measures in hospital settings.